Motivational teaching practices from EFL learners’ perspective at tertiary level in Yemen - Ahmed, Waleed Mohammed A.; Al-Ward, Ali Saleh (Indonesian Journal of Applied Linguistics, 2020)
Motivation is an important factor for success in learning a foreign or second language. Creating such motivation among learners through adopting certain teaching practices is likely to stimulate learners to learn. Previous research has largely investigated motivational teaching practices from the teachers’ perspective. However, little research has addressed motivational practices from the learners’ perspective. In a context such as Yemen, EFL teachers at the tertiary level encounter a challenging task in creating motivational practices for learners whose preferences for teaching practices should be the cornerstone in the learning and teaching process. Therefore, this study aimed to explore whether the teaching practices adopted by teachers are motivating from the learners’ perspective. To achieve this objective, a questionnaire was distributed to 137 undergraduate students in level four at the English Department within two faculties (i.e., Faculty of Education and Faculty of Languages) at Sana'a University. Data collected were analyzed using SPSS. The teaching practices which are likely to be motivating as perceived by learners were computed and compared. The findings revealed that teaching macro-practices vary in the degree of their motivation from most motivating (i.e., familiarize learners with L2 related values) to the least motivating (present tasks properly) as perceived by learners. The study also revealed that some teaching macro-practices appear to be transmitted to the Arab culture based on the learner-center approach.